FUELING JOB ENGINES: IMPACTS OF SMALL BUSINESS LOANS ON ESTABLISHMENT BIRTHS IN METROPOLITAN AND NONMETRO COUNTIES. (13th February 2017) - Conroy, Tessa; Low, Sarah A.; Weiler, Stephan
Abstract : This study examines the effect of small business loans on subsequent establishment births in U.S. counties. Using an economic growth framework and cross‐sectional empirical model, we test the hypothesis that the establishment birth rate is higher in counties where the level and annual increase in lending is greater, controlling for community‐level characteristics affecting business and economic dynamics. We also consider the long‐term effect of small business lending and focus on establishing the appropriate lag structure. The results indicate that small business lending does generally have a positive effect on the employer establishment birth rate that is strongest in nonmetropolitan (rural) counties. ( JEL L26, R11, M13)